Pengembangan Desain Fitting untuk Furnitur Kardus dengan Memanfaatkan Teknologi Pencetakan 3D - Abdul Gafur Maulana; Imam Damar Djati (Aliansi Desainer Produk Industri Indonesia (ADPII), 2025)
Cardboard furniture has emerged as a lightweight, easy-to-assemble, and efficient alternative for temporary use. However, the structural limitations of cardboard, particularly at panel joints, make it susceptible to deformation and damage due to external forces. This study aims to design and develop fittings as joint components to optimize the stability and strength of cardboard furniture. The fittings were developed using 3D printing technology with the Fused Deposition Modeling (FDM) method, utilizing a MakerBot Replicator 2 machine and MakerBot PLA filament. In this study, two fitting designs were developed, namely symmetric and asymmetric designs, which were then compared to determine the most optimal design. Finite Element Analysis (FEA) was used to evaluate the structural strength of both designs. The results showed that the symmetric design exhibited better resistance to tensile forces than the asymmetric design. In the symmetric design, the ultimate tensile strength (62 MPa) was reached at a tensile force of 46 N, while the asymmetric design only reached 44 N. Based on these findings, the symmetric design was selected as the foundation for developing 17 module variants, consisting of edge joints and corner joints with various configurations. These module variants enable diverse structural joint mechanisms in the assembly system of cardboard furniture and can also be applied to existing cardboard furniture as additional accessories to enhance its structural integrity.